2020
DOI: 10.1016/j.diii.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Three artificial intelligence data challenges based on CT and MRI

Abstract: Purpose: The 2019 edition of the data challenge was organized by the French Society of Radiology (SFR) during the Journées Francophones de Radiologie with the aim to: (i) work on relevant problematics of public health (ii) build large multicentric and prospective databases and (iii) boost the French AI community around radiologists. In comparison to the 2018 edition a first objective was to increase the question's complexity by including 3D information and prognostic analysis. The second objective was to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 33 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…These include the retrospective nature and single-center design of the study, as well as the subjective definition of the vascular sign. Future research efforts should aim to validate our findings in multi-center studies and explore the potential of artificial intelligence in overcoming limitations related to imaging resolution and observer subjectivity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include the retrospective nature and single-center design of the study, as well as the subjective definition of the vascular sign. Future research efforts should aim to validate our findings in multi-center studies and explore the potential of artificial intelligence in overcoming limitations related to imaging resolution and observer subjectivity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other challenges for lung nodule detection have been organized, for example: the data challenge held at the annual congress of the French Society of Radiology in 2019 (Journées Francophones de Radiologie 2019). This challenge included 1237 chest CT examinations and participants were asked to develop AI models that detected lung nodules; calculating their volume after segmentation and classifying them as either: probably benign (volume < 100 mm 3 ) or probably malignant (volume ≥ 100 mm 3 ) nodules [29,30].…”
Section: Lung Nodule Detectionmentioning
confidence: 99%
“…Data challenges on medical and clinical images have already been organized in recent years. We can mention those of French radiologists since 2018, 9 , 10 and the Camelyon 16 and 17 in pathology. 11 A recent review paper reported several data challenges in pathology and what these competitions brought to this speciality.…”
Section: Introductionmentioning
confidence: 99%